Embers and ashes : Oriya stories of marital blues and bruises - Mohapatra, Leelawati; Mohapatra, Leelawati (Grassroots Indian writers series, 2007)
Patent medicine / Fakir Mohan Senapati -- Bed of arrows / Gopinath Mohanty -- Companions in sorrow / Kishori Charan Das -- The visitor / Santanu Kumar Acharya -- The interlude / J.P. Das -- Flowering night / Binapani Mohanty -- The stigma / Pratibha Ray -- The descent / Tarun Kanti Mishra -- The couple / Sivapada Swain -- Moonlight / Yashodhara Mishra -- The rape / Sarojini Sahoo -- Crows / K.K. Mohapatra